Beyond tribulus (Tribulus terrestris L.): The effects of phytotherapics on testosterone, sperm and prostate parameters. (10th May 2019) - Santos, Heitor O.; Howell, Scott; Teixeira, Filipe J.
Abstract: Ethno-pharmacological relevance: Phytotherapeutic approaches have been widely proposed to improve male health. Despite the well-touted effects of tribulus (Tribulus terrestris L) on men's health, an optimal phytotherapy remains an elusive challenge. Aim of the review: We sought to critically analyze the evidence in the phytotherapic literature beyond the effects of tribulus on testosterone (T) concentration and sperm analysis to also include indications for prostate health. Materials and methods: A focused literature search was conducted to include studies published in Cochrane, Pubmed, and Web of Science databases between the years 2002 and 2018. Results: The use of tribulus and maca ( Lepidium meyenii Walp, Brassicaceae) were not scientifically supported to improve serum T levels in men. Moderate evidence supports the use of long Jack ( Eurycoma longifolia Jack, Simaroubaceae), mucuna ( Mucuna pruriens (L.) DC., Fabaceae), ashwagandha ( Withania somnifera (L.) Dunal, Solanaceae), fenugreek ( Trigonella foenum-graceum L., Fabaceae), and black seeds ( Nigella sativa L., Ranunculaceae) to increase total T and improve seminal parameters. Data suggests an increase in total T with the use of 5000 mg/d of powdered mucuna seed and ashwagandha root (151 and 143 ng/dL, respectively) over a 12-week period in patients with oligozoospermia. The use of mucuna was supported for patients with oligozoospermia to improve sperm parameters, with an increase of 83.3 million/mL observed after use of 5000 mg/d of powdered mucuna seed over a 12-week period. Evidence supporting the use of saw palmetto ( Serenoa repens, (W.Bartram) Small, Arecaceae) to improve prostate health remains equivocal; whereas, evidence supporting the use of Pygeum africanum Hook.f., Rosaceae, Urtica dioica L., Urticaceae, beta-sitosterols, pollen extract, onion, garlic, and tomato, appears favorable and promising. Conclusion: Scientific evidence supports the use of mucuna and ashwagandha as phytotherapics for improving serum T concentrations and semen parameters. Despite inconclusive evidence for use of tribulus as a T booster, it may provide advantageous effects on sperm parameters in men with idiopathic infertility. Nutraceutical strategies and some phytotherapics may also be effective to promote prostate health. Popular foodstuffs (onion, garlic, and tomato), nutraceutical agents (pollen extract and beta-sitosterols), and herbal medicines ( Pygeum africanum and Urtica dioica ) are rational approaches. Graphical abstract: fx1